Introducing Life Skills through Activities - Pahuja, Manisha Taneja (JOURNAL OF INDIAN EDUCATION, 2018)
Life skills are essentially those skills that help promote the overall well-being and competence in young people as they face the realities of life. We all use life skills in different situations, such as to negotiate effectively at home, school or workplace. When faced with difficult situations, we tend to think critically, analyse all the pros and cons of the situation, think out of the box to find a solution to seemingly difficult problems. Children learn their life skills from parents, teachers and significant others who act as their role model. That is why, the Life Skills Programme—a school-based programme, is imparted in different schools. This paper highlights the various classroom activities that must be practised and encouraged for understanding life skills better.